Relationship Between Upper Extremity Muscle Strength and Functional Level and Mobility in Patients with Ankylosing Spondylitis - Duygu Geler Külcü,; Müge Bıçakçıgil,; Gülçin Gülşen,; Demet Taşan,; Esra İmamoğlu,; Derya Özkan, (Archives of Rheumatology, 2009)
Objective: To assess muscle strength of upper extremity muscles in patients with ankylosing spondylitis (AS) and analyze any association between muscle strength and mobility and functional level. Materials and Methods: 30 patients diagnosed as AS and 20 healthy controls were included into the study. Demographics such as age, gender, body mass index, disease duration, and physical activity level were recorded. Mobility parameters [occiput-wall (OWD), chinsternum (CSD), finger-floor distances (FFD), modified Schober (MS), and chest expansion diameter (CED)] were evaluated in both groups. Deltoid anterior, trapezius middle, rhomboid and biceps muscle strength were measured by manual upper extremity-trunk dynamometer. Bath AS Functional Index (BASFI) and Bath AS Disease Activity Index (BASDAI) were used to evaluate functional level. Groups were compared by Mann–Whitney U test. The relationship between muscle strength and mobilization parameters and functional level were analyzed by Spearman correlation coefficient. Results: Mean age of the patients was 34.8±9.1 and the mean disease duration was 8.4±8.3 years (9/21: female/male). The mean age of controls was 34.0±7.3 years (7/13: female/male). All assessed mobilization parameters except CSD and OWD and muscle strengths except rhomboid muscle were significantly lower in patients (p<0.05). In the patient group, biceps muscle strength was associated with MS (r=0.480, p=0.038), CED (r=0.472, p=0.011), and inversely with FFD (-0.628, p=0.000). Middle trapezius muscle strength was associated with MS (r=0.621, p=0.005) and inversely with FFD (r=-0.610, p=0.001). Anterior deltoid muscle strength was associated with MS (r=0.383, p=0.044), CED (r=0.513, p=0.005), and inversely with FFD (r=-0.645, p=0.000) and CSD (r=-0.498, p=0.008). Rhomboid muscle strength was associated with MS, CED (r=0.421, p=0.026), and inversely with FFD (r=-0.504, p=0.006). No correlation was found between measured muscle strength and BASFI and BASDAI scores. Conclusion: Upper extremity muscle strengths decrease in patients with AS. There is an association between upper extremity muscle strengths and mobility. (Turk J Rheumatol 2009; 24: 82-7)